Subseafloor Biosphere Linked to Hydrothermal Systems 2014
DOI: 10.1007/978-4-431-54865-2_29
|View full text |Cite
|
Sign up to set email alerts
|

ESR Dating of Barite in Sea-Floor Hydrothermal Sulfide Deposits in the Okinawa Trough

Abstract: ESR (electron spin resonance) ages were determined for barite crystals extracted from hydrothermal sulfide deposits taken at Daiyon-Yonaguni Knoll field, Hatoma Knoll field, Iheya North Knoll field, Hakurei Site of Izena Hole field, Yoron Hole field of the Okinawa Trough. The ages range from 4.1 to 16,000 years, being consistent with detection of 228 Ra in younger samples and radioactive equilibrium/disequilibrium between radium and daughter nuclei. The variation of the ages within each sample is mostly within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…In the present study, high haplotype diversity was observed for each local population of S. leurokolos (haplotype diversity: 0.98 to 1.00) and no genetic differentiation was detected among the local populations. S. leurokolos is assumed to have a high colonisation ability compared to the other 3 alvinocaridids because this species (1) is broadly distributed both spatially and bathymetrically and (2) rapidly colonised a newly developed hydrothermal vent site at Yoron Hole, where all of the collected chimneys and ores are < 400 yr in age (Fujiwara et al 2015). Another dominant decapod species in the Okinawa Trough, Shinkaia crosnieri, also has high genetic diversity (Kumagai et al 2015).…”
Section: Genetic Diversity and Population Expansionmentioning
confidence: 99%
“…In the present study, high haplotype diversity was observed for each local population of S. leurokolos (haplotype diversity: 0.98 to 1.00) and no genetic differentiation was detected among the local populations. S. leurokolos is assumed to have a high colonisation ability compared to the other 3 alvinocaridids because this species (1) is broadly distributed both spatially and bathymetrically and (2) rapidly colonised a newly developed hydrothermal vent site at Yoron Hole, where all of the collected chimneys and ores are < 400 yr in age (Fujiwara et al 2015). Another dominant decapod species in the Okinawa Trough, Shinkaia crosnieri, also has high genetic diversity (Kumagai et al 2015).…”
Section: Genetic Diversity and Population Expansionmentioning
confidence: 99%
“…The barite crystals occur in sulfide chimneys and in deposits, incorporating radium ions that are in the hydrothermal fluid. As a radium ion has an ionic radius similar with barium, radium ions easily replace barium in barite to have high concentration up to several tens Bq/g of 226 Ra (Fujiwara et al, 2015).…”
Section: Issues In Determining Dose Rates To Barite Extracted From Sementioning
confidence: 99%
“…They showed that the ESR ages are roughly consistent with the U-Th ages. While Toyoda et al (2014) discussed several detailed technical issues such as the dose rate conversion factors, the sample edge effect for gamma ray dose, and the correction for the decay of 226 Ra, Fujiwara et al (2015) made the first practical systematic dating work with ESR on barite of sea-floor hydrothermal sulfide deposits taken at Okinawa Trough on total of 18 samples (60 subsamples) with new formulas which take the radioactive disequilibrium of Ra daughter nuclei into account. The obtained ages range 4 to 16000 years, showing that the ESR method has a wide application age range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various dating techniques have been employed, such as U-Th method on sulfide minerals (Takamasa et al 2013), ESR method on barite (Takamasa et al 2013;Fujiwara et al (2014), Chap. 34), and 226 Pb,228 Th method on barite (Noguchi et al 2004;Uchida et al (2014), Chap.…”
Section: Introductionmentioning
confidence: 99%